Estimator's electrical man-hour manual - Page, John S. (Gulf Professional Pub., 1999)
Makes accurate, reliable man-hour estimates for electrical installation. This new edition is revised and expanded to include installation of electrical instrumentation, which is used in monitoring various process systems. Branch, service, and feeder rough-in. Branch, service, and feeder wiring. Wiring devices-switches, outlets, and receptacles. Surface metal raceway and branch busway. Lighting fixtures. Underfloor ducts. Bus ducts. Electric heating and ventilating. Panelboards and accessories. Switchboards and accessories. Switches, starters, controls, and gutters. Motor control centers. Motor controls and motors. Power transformers. Outside overhead systems. Outside underground systems. Communications and signal systems. Electrical instrument installation. Anchors, fasteners, hangers, and supports. Demolition, excavation, and concrete. Technical information.